Characterization of Nutritional, Antinutritional, and Mineral Contents of Thirty-Five Sorghum Varieties Grown in Ethiopia - Masresha Minuye Tasie; Belay Gezahegn Gebreyes (International Journal of Food Science)
An experiment was carried out to characterize the proximate compositions and antinutritional and mineral contents of sorghum varieties released for production by the Ethiopian sorghum improvement programme. Sorghum is an extensively researched crop in Ethiopia. However, comprehensive information on nutritional, antinutritional, and mineral content has not been generated. In the present study, thirty-five sorghum varieties released by the national sorghum improvement programme were used and evaluated for their proximate compositions, tannin, and mineral nutrient. AOAC methods of analysis were used for proximate compositions and mineral content together, i.e., whereas for tannin, vanillin-HCL assay methods of analysis were used. Differences between sorghum varieties were significant (P≤0.05) for all measured parameters. Proximate composition values such as moisture, ash, crude fat, crude fiber, crude protein, and CHO varied from 9.66 to 12.94, 1.12 to 2.29, 2.48 to 4.60, 2.17 to 8.59, 8.20 to 16.48, and 67.56 to 76.42, respectively. The highest mineral content of P (367.965), Na (6.151), Mg (207.526), K (314.011), Ca (67.159), Fe (14.018), and Zn (6.484) as measured by mg/100 g was found from the varieties Macia, Abshir, Chiro, Birmash, Dagem, and Assossa-1 (Fe and Zn), respectively. Maximum tannin values of 3337.200 and 2474.7 mg/100 g were obtained from Lalo and Dano, respectively. The varieties such as Miskir, Abshir, ESH-1, Meko-1, Red Swazi, and Karimtams have higher nutritional and mineral and lower antinutritional values among the tested varieties. The abovementioned varieties should be considered for food product development due to their nutritional qualities.